The Effectiveness of Brainstorming Methods Through KIA Book Media in Increasing Pregnant Women's Knowledge About 1000 HPK to Prevent Stunting - Mardiansyah, Mardiansyah; Abdi, Lalu Khairul; Saimi, Saimi (poltekkes kemenkes mataram, 2024)
In West Nusa Tenggara the prevalence of stunting is placed seventh with a frequency of 33.49%, whereas the prevalence of stunting in Indonesia is 30.8%, according to Riskesdas 2018. A useful strategy for raising awareness and preventing stunting problems is to use KIA book media to facilitate brainstorming sessions for 1000 HPK. To ascertain the impact of counseling on 1000 HPK (First Day of Life) participants' knowledge of reducing stunting at the Narmada Community Health Center Working Area through the use of the KIA book media and the brainstorming approach. Nonequivalent Control Group Design is the research method utilized in quasi-experimental design studies. There were 112 research targets as the research subjects. A questionnaire was the tool utilized. The independent sample t-test and the paired sample t-test were used to test the data. Findings from Research. There were four people (7.14%), eighteen people (32.14%), and thirty-four people (60.71%) who knew about pregnant women before treatment for the poor category. Following the intervention, it rose to fall into one of three categories: less than none, moderate (consisting of 11 individuals/19.64%), and good (consisting of 45 individuals (80.36%). The results of statistical tests utilizing the paired sample t-test show that there is a significant influence between the usage of KIA book media at 1000 HPK and brainstorming approaches, with a p value of 0.000 < 0.05. Pregnant women's knowledge increased after counseling with the brainstorming method using KIA book media, according to the analysis's results, which also indicate a substantial difference in the women's knowledge before and after counseling.